Direct Funding and the Depoliticization of Home Care Systems: Popular Rhetoric and Policy Directions in Ontario - Hande, Mary Jean; Jamal, Aliya; Kelly, Christine (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2020)
Home care systems have undergone major transformation in the last twenty years, manifesting as a volatile series of policy changes in Ontario, Canada. This includes increasing attention to direct funding (DF) home care where individuals receive cash transfers to arrange their own services. Through a textual analysis of 101 media and grey literature sources about DF home care in Ontario published between 2011 and 2018, we find three interrelated, yet sometimes conflicting, discourses in public circulation. DF is represented as: (1) a ‘fix’ to the challenges of mainstream home care; (2) a form of marketization; and (3) as social transformation. We argue that these discourses reflect a neoliberal policy climate that depoliticizes and instrumentalizes DF in ways that obscure how continual policy adjustments actually contribute to frustrating experiences with home care. The contradictory claims about DF home care in the public domain often untether DF from its social justice history and from the careful implementation needed for it to be an empowering and equitable home care model. We suggest that DF home care should not be approached primarily as an individual fix to systemic problems with home care nor as a strategy for cost saving. Rather, DF should be one component of a broad spectrum of social care policies that fully acknowledge both the social justice history of the program and the complex interdependencies of home care users, workers and informal caregivers. Résumé Les systèmes de soins à domicile ont connu une importante transformation au cours des vingt dernières années, engendrant une série de changements politiques en Ontario (Canada), dont une attention croissante au financement direct (FD) des soins à domicile où les individus reçoivent des fonds pour gérer leurs propres services. En analysant 101 textes des médias et de la littérature grise au sujet du FD des soins à domicile, nous trouvons trois discours en libre circulation qui sont étroitement liés mais parfois contradictoires. Le FD est présenté comme étant (1) une « solution » aux défis que posent les soins à domiciles traditionnels, (2) une forme de marchéisation et (3) une transformation sociale. Nous soutenons que ces discours sont le reflet d’un milieu politique néo-libérale qui dépolitise et instrumentalise le FD de manière à masquer la façon dont l’ajustement continu des politiques concourt réellement aux expériences frustrantes liées aux soins à domicile. Les affirmations contradictoires au sujet du FD des soins à domicile du domaine public détachent souvent le FD de son histoire de justice sociale et de la mise en œuvre minutieuse nécessaire pour qu’il devienne un modèle de soins à domicile responsabilisant et équitable. Nous proposons que le FD des soins à domicile ne soit pas abordé comme une solution individuelle aux problèmes systémiques liés aux soins à domicile ou comme une stratégie visant à réduire les coûts, mais plutôt comme faisant partie d’un large éventail de politiques d’assistance sociale qui reconnaît pleinement l’histoire de justice sociale du programme ainsi que l’interdépendance complexe entre les usagers des soins à domiciles, les travailleurs et les aidants naturels. Mots clés: vieillissement; Canada; invalidité; soins autogérés